The stand for dynamic researches of hydrounits of the hinged equipment of soil-cultivating technics - Гасюк, Александр Иванович; Цента, Евгений Николаевич (Eastern-European Journal of Enterprise Technologies, 2010)
Article is devoted working out of the experimental hydraulic stand for carrying out of dynamic researches of the hydrounit of the hinged equipment a tractor. At the stand there is a possibility of change in a wide range of loading on working body with high degree of speed.